2016
DOI: 10.1007/s11999-015-4424-5
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Reoperations at 2 Years Between Ceramic-on-metal and Metal-on-metal THA: A Randomized Trial

Abstract: Background Hard-on-hard bearings for total hip arthroplasty continue to warrant analysis even though crosslinked polyethylene is performing very well. Ceramicon-metal (CoM) has low in vitro wear and did well in an early clinical trial. We report on a prospective, randomized, multicenter investigational device trial comparing CoM with metal-on-metal (MoM). Questions/purposes (1) Is there a difference in the number or type of revisions comparing CoM with MoM? (2) Are cobalt and chromium metal levels different fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…However, failures associated with MoM/CoM implants are not necessarily due to the bearing surface itself only, but other potential reasons such as implant loosening, taper junction failures, and infection may also play a critical role . In this study, no malposition of the cups was found since the metal liner was yet well fixed and stable in the acetabulum.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…However, failures associated with MoM/CoM implants are not necessarily due to the bearing surface itself only, but other potential reasons such as implant loosening, taper junction failures, and infection may also play a critical role . In this study, no malposition of the cups was found since the metal liner was yet well fixed and stable in the acetabulum.…”
Section: Discussionmentioning
confidence: 57%
“…In a double‐blinded randomized study, Schouten et al compared chromium and cobalt release in patients treated with CoM ( n = 41) and MoM ( n = 36) bearings but found no differences, after 6 and 12 months. Such comment was also made by Engh et al in addition to a similar number or type of revisions comparing CoM with MoM THAs . In contrast, Hill et al reported the presence of radiolucent lines and higher than expected levels of metal ions in the blood from the study of a total of 287 CoM THAs, and Zeng et al claimed that the use of a CoM THA was clinically effective and metal ion levels were significantly elevated at midterm follow‐up .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Several in vitro analyses showed a lower risk of implant fracture, reduced wear, and metal debris, as well as squeaking phenomena compared to CoC and MoM bearings [2, 57, 9]. …”
Section: Introductionmentioning
confidence: 99%